Clinical Evaluation of Anti-Wrinkle Cosmetics containing Enhanced Solubilized System on Adenosine using Mixed Hydrotropic Agents - Su In Park; Kwang Won Lee; Jeong-Lae Kim; Moon Sam Shin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Adenosine is a typical active ingredient in wrinkle improvement functional cosmetics. However, adenosine has significant problems in producing formulations with sufficient bioavailability due to its low aqueous solubility. To overcome this problem, using niacinamide and vanillin mixed hydrotropic solubilization technique, which lower the minimum hydrotrope concentration (MHC) for adenosine, we developed cosmetics containing 2 % adenosine, and then clinical effect on wrinkle improvement and moisturizing of the cosmetics was evaluated. As a result of measuring crow's feet, skin moisture content, and transepidermal water loss (TEWL), 1) the improvement rate of crow's feet after 2 weeks and 4 weeks was 6.984 % and 10.609 %, respectively (p<0.05); 2) the improvement rate of the skin moisture content after 2 weeks and 4 weeks was 8.871 % and 15.576 %, respectively (p<0.05); 3) the improvement rate of the TEWL after 2 weeks and 4 weeks was 10.685 % and 9.498 %, respectively (p<0.05). In other words, we maximized the wrinkle improvement effect of adenosine by increasing the aqueous solubility using mixed hydrotropic agents.